Fertilización bioorgánica y su efecto en las características agronómicas y captura de carbono del pasto castilla en Zungarococha 2021 - Bazan Pacaya, Arturo (2022)
The work was developed in the shop agrostology of the agronomy ability, evaluating the grass castile to the 6ta week, the objective was to determine if the fertilization bioorganica influences in the agronomic characteristics and capture of carbon, the population was conformed by 800 plants of the studied species and the dbca was used with 5 treatments and 4 repetitions, the work was of quantitative type and of experimental design, reaching the following conclusions; that if effect of the fertilization bioorganica applied to the grass castilla just as the t4 exists it indicates it (i pasture more castilla amaciza, gliricidia, button of gold, gallinaza and 50 worms) who occupied the first position of order of merit with averages of 6.70 (kg/m2) of green matter (430 g/m2) of dry matter and (0.17 kg/m2) of carbon.